United Kingdom : Financial Sector Assessment Program-Insurance Sector-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides an assessment of the insurance sector in the United Kingdom. The United Kingdom has one of the deepest, most developed insurance markets in the world. Insurance penetration is 50 percent higher than in the European Union or other advanced economies, and the expenditure per capita in insurance amounts to USD 5,429 as compared with USD 3,815 in the advanced economies. The supervisory approach of both the Prudential Regulation Authority and the Financial Conduct Authority (FCA) are forward-looking and risk-based. However, improved data availability and an enhanced risk appetite statement are required. Notwithstanding stronger enforcement on supervisory and enforcement actions, important challenges still need to be addressed by the FCA.